Relative weight and disability retirement: a prospective cohort study - Eira Roos; Mikko Laaksonen; Ossi Rahkonen; Eero Lahelma; Tea Lallukka (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVES: The aims of this study were to examine (i) the association of relative weight with subsequent disability retirement due to any diagnosis and also in two major diagnostic groups (ie, musculoskeletal diseases and mental disorders) and (ii) whether diagnosed diseases, physical and mental functioning, and working conditions explain these associations. METHODS: This prospective study comprised a cohort of 6542 middle-aged employees of the City of Helsinki, Finland. Questionnaire data were linked with register data on disability retirements, with a mean follow-up time of 7.8 years. RESULTS: Adjusting for age, body mass index (BMI) was associated with all-cause disability retirement among men and women, the highest risk being for the severely obese and the obese [hazard ratio (HR) 3.45, 95% confidence interval (95% CI) 2.53-4.69; HR 1.94, 95% CI 1.52-2.46, respectively]. Adjusting for age, relative weight was also strongly associated with the main retirement diagnoses, especially musculoskeletal diseases among the severely obese (HR 4.76, 95% CI 3.06-7.40) and obese (HR 2.35, 95% CI 1.62-3.39). The association was attenuated when adjusting for self-reported diseases and physical and mental functioning at baseline. Working conditions had negligible effects on the associations. CONCLUSIONS: Maintenance of normal weight is likely to reduce the risk of disability retirement. Among obese employees, the focus should be on the improvement of physical functioning and the effective treatment of obesity and its co-morbidities to counteract the heightened risk of disability retirement.